Eco fashion - Brown, Sass (London : Laurence King, 2010)
Chapter 1 Community & Fair Trade: Alabama Chanin / Amana / El Naturalista / Elena Garcia / Leila Hafzi / Les Fées de Bengale / ModaFusion / Mona Mohanna / Noir / Royah / sense-organics / Shoto Banerji / Taller Flora / Van Markoviec -- ##Chapter 2 Ecological & Slow Design: Alexandra Faro / Camila Norrback / Céline Faizant / Christine Birkle / Ciel / Emily Katz / Enamore / FIN / Françoise Hoffmann / Linda Loudermilk / Magdalena Schaffrin / RoyalBLUSH / Samant Chauhan / U Roads / YOJ -- ##Chapter 3 Recycle, Reuse & Redesign: Angela Johnson / Costumisée par Liza / Demano / E2 / Frau Wagner / From Somewhere / Geoffrey B. Small / Josh Jakus / Preloved / Rebound Designs / Riedizioni / Stephan Hann / Suitcase / TRAIDremade -- ##Chapter 4 New Models: aforest-design / Andrea Zittel / Bless / Collection of Hope / Holly McQuillan / Mark Liu / Nau / Rebecca Earley & Kate Goldsworthy / Redesign the World -- ##Chapter 5 Designer & Corporate Initiatives: Agatha Ruiz de la Prada / Barneys New York / H&M and Designers Against Aids / Katharine Hamnett / Miguel Adrover / Philippe Starck / Salvatore Ferragamo / Vivienne Westwood / Yeohlee Teng / Yves Saint Laurent
boek